(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2018)
Skinner proposed a functional treatment of language, defining verbal behavior as behavior established and maintained by mediated consequences, provided by a listener especially trained by a verbal community. He also presented a taxonomy of this kind of behavior: primary operants - mand, tact, echoic, intraverbal, transcription and textual - and secondary - autoclitic. There are few experimental studies about autoclitics, what can be harmful to the area, since autoclitic is essential in comprehension of complex verbal repertories. The reduced frequency can be the result of its complexity and comprehension, because of the intricate and distributed form of its treatment throughout Verbal Behavior. This paper presents the treatment offered by Skinner to autoclitic, in an integrated way. This systematization might assist the comprehension of the theme and stimulate new researches. In this sense, possible uses of this interpretation to development of researches and intervention in Applied Behavior Analysis are indicated.